2023
DOI: 10.1615/jenvironpatholtoxicoloncol.2022045134
|View full text |Cite
|
Sign up to set email alerts
|

METTL14 Promotes Oral Squamous Cell Carcinoma Progression by Regulating the mRNA and m6A Levels of CALD1

Abstract: Oral squamous cell carcinoma (OSCC) still threatens people's daily life. METTL14 is a newly discovered methyltransferase that catalyzes m6A methylation. Hence, this research was carried out to investigate the action mechanism of METTL14 in OSCC. The SCC-4 and UM2 cells, and tumorigenicity assay were utilized to investigate METTL14 roles <i>in vitro</i> and<i> in vivo</i>. Bioinformatic analysis was carried out with the UCSC, TCGA database and The Human Protein Atlas. The gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Chen et al [15] found that METTL3-mediated ALDH m6A methylation regulated the malignant behavior of BMI1+ HNSCC stem cells. Moreover, METTL14 promoted oral squamous cell carcinoma progression by regulating the mRNA and m6A levels of CALD1 [16]. Pan et al [17] found that METTL3-enhanced dentinogenesis differentiation of dental pulp stem cells via increasing GDF6 and STC1 mRNA stability.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [15] found that METTL3-mediated ALDH m6A methylation regulated the malignant behavior of BMI1+ HNSCC stem cells. Moreover, METTL14 promoted oral squamous cell carcinoma progression by regulating the mRNA and m6A levels of CALD1 [16]. Pan et al [17] found that METTL3-enhanced dentinogenesis differentiation of dental pulp stem cells via increasing GDF6 and STC1 mRNA stability.…”
Section: Introductionmentioning
confidence: 99%